Prediction of the potential geographical distribution of Cytospora chrysosperma in Xinjiang, China under climate change scenarios - Li, Quansheng; Cao, Shanshan; Sun, Wei; Zhang, Zhiyong (Frontiers in Forests and Global Change, 2024)
Cytospora canker caused by Cytospora chrysosperma has a wide range of hazards in Xinjiang, seriously affecting the development of Xinjiang’s characteristic forest and fruit industries. Climate change affects the distribution of fungal species and may exacerbate the risk of forest diseases such as cytospora canker. The present study was conducted on C. chrysosperma and makes predictions of potentially suitable area based on 133 records of C. chrysosperma distribution points and 47 environmental factors. We applied the MaxEnt model adjusted by the Kuenm package for feature class parameters (FC) and regularization multipliers (RM) to explore the main environmental factors affecting the geographical distribution of C. chrysosperma. And then we predicted its spatial distribution pattern and centroid change trend in potentially suitable area under three different Representative Concentration Pathways in the current scenario, 2041–2070, and 2071–2,100. The results showed that the optimal model with parameters FC = LQ and RM = 0.3 had the lowest model complexity and overfitting, and the model predicted with very high accuracy, AUC = 0.971 ± 0.0019. Considering the percent contribution, permutation importance of jackknife and single-factor response curve, the main environmental factors affecting its geographical distribution are precipitation seasonality (bio15), aspect cosine (aspectcosine), monthly variability in potential evapotranspiration (PETseasonality), and mean monthly potential evapotranspiration of the coldest quarter (PETColdestQuarter), with a cumulative contribution rate reaching 70.8%. Under the current climate scenarios, the total suitable area for C. chrysosperma is 82.35 × 104 km2, and the highly suitable area is 5.49 × 104 km2, accounting for 6.67% of the total suitable area, primarily located in the Tacheng, Yili, and Changji regions. Meanwhile, centroid transfer analysis indicates a tendency for its distribution to migrate towards lower latitudes under future climatic conditions. The MaxEnt model proposed in this study can be used to predict the distribution and risk of C. chrysosperma in Xinjiang and provide guidance for the prevention and control of cytospora canker.